2015
DOI: 10.1136/medethics-2015-102856
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Rasouli decision: a Survey of Canadian intensivists

Abstract: Many Canadian ICU physicians report providing a higher intensity of treatment, and less subjectively appropriate treatment, in situations of dispute over EoL care after the Supreme Court of Canada's ruling in Cuthbertson versus Rasouli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The lack of documentation of value considerations concerns us and will be followed up. In Canada, the legal requirement for consent from families for patients without a decision-making capacity differs from the Norwegian legislation and may explain differences in chart documentation practices [41]. …”
Section: Discussionmentioning
confidence: 99%
“…The lack of documentation of value considerations concerns us and will be followed up. In Canada, the legal requirement for consent from families for patients without a decision-making capacity differs from the Norwegian legislation and may explain differences in chart documentation practices [41]. …”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, passage of the “well-dying law” was associated with an improvement in the quality of death and dying in South Korean intensive care units (ICUs) as perceived by ICU clinicians . In Canada, the 2013 Supreme Court decision in Cuthbertson v Rasouli deemed the consent of the patient or substitute decision maker mandatory in certain circumstances to withdraw life support . A study using clinical vignettes to compare care choices of Canadian ICU physicians prior to and after the ruling demonstrated that after the Rasouli decision, physicians shifted to choosing courses of treatment that were of higher intensity and less “appropriate” (based on their subjective characterization) .…”
Section: Discussionmentioning
confidence: 99%
“…38 In Canada, the 2013 Supreme Court decision in Cuthbertson v Rasouli deemed the consent of the patient or substitute decision maker mandatory in certain circumstances to withdraw life support. 39,40 A study using clinical vignettes to compare care choices of Canadian ICU physicians prior to and after the ruling demonstrated that after the Rasouli decision, physicians shifted to choosing courses of treatment that were of higher intensity and less "appropriate" (based on their subjective characterization). 39 However, passage of a law also does not necessarily lead to the desired change in individual behavior.…”
Section: Relative Risk (95% Ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ruling rested in part on Ontario's Health Care Consent Act (HCCA), the policy of the College of Physicians and Surgeons of Ontario and hospital policies, it has implications for practice across Canada. 2 Furthermore, it emphasizes the importance of policy as part of the court's determination of the standard of care. The Wawrzyniak case also addressed the common law, which is not binding outside Ontario, but may be persuasive, especially in jurisdictions where the case law on consent is unclear.…”
mentioning
confidence: 99%